Hubungan perubahan iklim dengan ketahanan pangan di indonesia - Biari, Dina Audina Hasan (Maliki Interdisciplinary Journal, 2025)
Climate change significantly impacts Indonesia’s agricultural sector and food security. Rising global temperatures, shifting rainfall patterns, and increased frequency of extreme weather events, such as droughts and floods, disrupt crop production cycles. This research utilizes literature review methods to explore how phenomena like El Niño and La Niña extend dry seasons or shorten rainy periods, affecting the growing season, crop quality, and food availability. Data shows that staple crops like rice, corn, and soybeans suffer from production losses due to climate stress and increased pest infestations, jeopardizing national food security. The climate’s unpredictability also drives food price volatility, affecting access and affordability for the population. For instance, in 2023, a severe El Niño led Indonesia to escalate rice imports, making it one of the world’s top importers. To address these challenges, adaptation strategies such as smart agriculture, development of climate-resilient crop varieties, and efficient irrigation have been implemented. These strategies are critical to maintaining Indonesia’s food production stability amid increasingly uncertain climate conditions.